Socio-scientific issues implementation as science learning material - Marlina Ummas Genisa; Bambang Subali; Djukri Djukri; Andi Agussalim; Habibi Habibi (International Journal of Evaluation and Research in Education (IJERE), 2020)
This paper analyzes the implementation of socio-scientific issues (SSI) as an alternative in science learning. The content analysis approach is used for mapping implementation of social-scientific problems around the world and is created using the ArcGIS 10.5 program. The findings highlight how the distribution patterns of SSI implementation are dominated by argumentation and decision making in SSI research. Teacher professional development related to SSI implementation also showed positive results for planning, developing, and solving problems related to SSI instruction. This study contributes as literature in exploring the implementation of SSI in educational contexts because its integration in science teaching materials is unfamiliar.